Information effect of entry into credit ratings market: The case of insurers' ratings - Doherty, Neil A.; Kartasheva, Anastasia V.; Phillips, Richard D. (Journal of Financial Economics, 2012)
The paper analyzes the effect of competition between credit rating agencies (CRAs) on the information content of ratings. We show that a monopolistic CRA pools sellers into multiple rating classes and has partial market coverage. This provides an opportunity for market entry. The entrant designs a rating scale distinct from that of the incumbent. It targets higher-than-average companies in each rating grade of the incumbent's rating scale and employs more stringent rating standards. We use Standard and Poor's (S&P) entry into the market for insurance ratings previously covered by a monopolist, A.M. Best, to empirically test the impact of entry on the information content of ratings. The empirical analysis reveals that S&P required higher standards to assign a rating similar to the one assigned by A.M. Best and that higher-than-average quality insurers in each rating category of A.M. Best chose to receive a second rating from S&P.